Synthesis Method of Control System for Spatial Motion of Autonomous Underwater Vehicle - Filaretov, Vladimir; Yukhimets, Dmitry (International Journal of Industrial Engineering and Management, 2012)
The article deals with to the synthesis of autonomous underwater vehicle spatial motion control system on the basis of the decomposition principle. The entire control system is divided into six control subsystems with separate degrees of freedom. In turn, each subsystem consists of three control loops: the thruster control loop, the vehicle’s velocity control loop and the control loop of its position. The paper proposes different methods of synthesis of controllers for each of these loops. The mathematical simulation confirms that the synthesis strategy selected was correct and shows the high efficiency of the obtained control system. Article history: Received (22 July 2012); Revised (16 September 2012); Accepted (24 September 2012)